2008
DOI: 10.1242/jeb.017616
|View full text |Cite
|
Sign up to set email alerts
|

Linear and nonlinear processing in hair cells

Abstract: SummaryMechanosensory hair cells in the ear are exquisitely responsive to minute sensory inputs, nearly to the point of instability. Active mechanisms bias the transduction apparatus and subsequent electrical amplification away from saturation in either the negative or positive direction, to an operating point where the response to small signals is approximately linear. An active force generator coupled directly to the transducer enhances sensitivity and frequency selectivity, and counteracts energy loss to vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 56 publications
1
14
0
Order By: Relevance
“…(11) and (12). The present transmission line model shows forward traveling waves for the primary tones f 1 and f 2 and a forward and backward traveling wave for the DP 2 f 1 À f 2 , where a two tone pair is presented in Fig.…”
Section: Comparison Of Transmission Line Model Andmentioning
confidence: 66%
See 3 more Smart Citations
“…(11) and (12). The present transmission line model shows forward traveling waves for the primary tones f 1 and f 2 and a forward and backward traveling wave for the DP 2 f 1 À f 2 , where a two tone pair is presented in Fig.…”
Section: Comparison Of Transmission Line Model Andmentioning
confidence: 66%
“…The IHCs transform mechanical information to neural information, whereas the OHCs amplify the BM motion. Mechanoelectric transduction by the OHCs produces a saturation function and is thought to represent the origin of nonlinearities in the cochlea [12]. Thus, the functions of the OHCs are the amplification and saturation of the BM motion.…”
Section: Transmission Line Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…It is reported that the compressive or tensile component of stresses dominates the responses of cutaneous Ad-fiber nociceptor (Khalsa et al 2000;Zheng et al 2002). While the relationship between stresses and receptor current is unknown-because the nociceptors is not accessible to whole-cell recording, sensory cells such as hair cells and pain receptors exhibit sigmoidal stimulus-current curves (Holt and Corey 2000;Roberts and Rutherford 2008;Siemens et al 2006), and the same trend of tension-Voltage for muscles exists (Karagueuzian and Katzung 1982). For this reason, this work employs a sigmoidal function…”
Section: Transduction Sub-modelmentioning
confidence: 99%